Conflict-minimal routing for free-ranging transportation vehicles in in-house logistics based on an a-priori lane design. (October 2021) - Reith, Karl-Benedikt; Rank, Sebastian; Schmidt, Thorsten
Highlights: Routing of free ranging vehicles consists of route planning and motion coordination. The presented lane concept is a novel approach for route planning. Lanes lead to short travel distances and a low amount of routing conflicts. The publication presents a design approch, applicable to real-world sized problems. A test case shows feasibility and advantages of lanes compared to benchmarks. Abstract: The routing of a fleet of autonomous and free ranging vehicles in in-house logistics is a complex task. Generally speaking, routing requires the determination of routes between sources and sinks (route planning) and rules to deal with detecting and solving routing conflicts between vehicles during operation (dynamic motion coordination). This publication introduces a new, lane-based approach for routing of free ranging vehicles. It bases on the idea of an a-priori design of multiple lanes, whereas a single lane is defined as a static, unidirectional and plane connection between a specific start and destination point in the layout. The basic idea of the described lane concept is to achieve short travel distances and low probabilities of routing conflicts for a fleet of free ranging vehicles. Accordingly, this paper also presents an appropriate heuristic for lane design and discusses its benefits compared to an exact approach in the context of applicability for real world sized problems. Further, an application in a test case shows the advantages of the lane-based routing, such as a lower amount of routing conflicts, lower transportation times and therefore an overall higher transportation system performance compared to two benchmark strategies for routing.